Disambiguation of neutralized forms in two Croatian varieties - Josipović, Višnja (Array, 1994)
This paper deals with the strategies of disambiguation of neutralized final obstruents observed in the speakers of two varieties of Croatian – Kajkavian vs. Standard. An experimental research was conducted to show how Eliasson's (1991) hypothesis about a cognitive calculus that is complementary to phonological rules applies to these two varieties. The results of the psycholinguistic test show that Eliasson's hypothesis holds true for the two varieties under consideration and prove the priority of those rules that were acquired earlier on the cognition of new language material.